Respuesta :

Answer:

  28) -1

  29) 9

  30) x^2+4x+7

  31) x-2

Step-by-step explanation:

Given:

  f(x) = x + 2

  g(x) = x^2 +3

Find:

  28) f(-3)

  29) f(g(2))

  30) g(f(x))

  31) f-1(x)

Solution:

Put the function argument values into the expression and do the arithmetic.

28) f(-3) = (-3) +2 = -1

__

29) f(g(2)) = f((2)^2 +3) = f(7) = (7) +2 = 9

__

30) g(f(x)) = g(x+2) = (x+2)^2 +3 = x^2 +4x +7

__

31) The meaning of y = f^-1(x) is x = f(y).

  x = f(y) = y+2

  y = x -2

  f^-1(x) = x -2